2003
DOI: 10.17660/actahortic.2003.628.99
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Vapours to Complement or Replace Sulfur Dioxide Fumigation of Table Grapes

Abstract: Recent studies have shown that dipping table grapes in ethanol solutions at harvest improved storage of the fruit. We report here the first results obtained by treating 'Chasselas' table grapes (Vitis vinifera) with ethanol vapours over the storage period. We tested the effect of ethanol at 0, 4 and 8 g/kg fruit during cold storage for 2, 4 and 6 weeks. We measured berry shatter, stem browning, Botrytis rot incidence and sensory appreciation by tasting panels. Ethanol vapours reduced Botrytis rot incidence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…In the preliminary study (Chervin et al, 2003), we showed that ethanol vapours also had the potential to reduce berry shatter. It would be worth checking this with other cultivars than 'Chasselas'.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In the preliminary study (Chervin et al, 2003), we showed that ethanol vapours also had the potential to reduce berry shatter. It would be worth checking this with other cultivars than 'Chasselas'.…”
Section: Resultsmentioning
confidence: 90%
“…We have already investigated the efficacy of ethanol vapours to control rots. Preliminary results indicated that the optimal ethanol dose for effective disease control was less than 5 ml.kg -1 of fruit (Chervin et al, 2003). Since stem browning was higher at 5 ml ethanol.kg -1 compared to SO 2 treatments, we conducted new experiments in order to find a lower dose of ethanol that would still control rot development without too high stem browning as in commercial SO 2 treatments,.…”
mentioning
confidence: 99%
“…The use of active films for food packaging applications represents a good option for the purposes of lengthening the food shelf life while maintaining quality [1,2]. The use of active films mitigates the drawbacks associated with the direct application of the antimicrobials on the food products, usually carried out by spraying or dipping, such as the rapid neutralization of active compounds or the fast diffusion from the surface into the product [3].…”
Section: Introductionmentioning
confidence: 99%
“…These include postharvest physical treatments [13,14] , modified atmosphere packaging [15][16][17] , temperature conditioning [18] and chemical treatments with plant growth regulators. [19][20][21][22] In this case, nitric oxide (NO) due to its properties (small size, no charge, short-lived, free radical and highly diffusible across biological membranes) has multifunctional roles in plant growth and mechanisms [23] and involved many plant physiological processes. [24,25] NO protects plant cells against oxidative stress by reducing ROS accumulation.…”
Section: Introductionmentioning
confidence: 99%